2011
DOI: 10.1186/1532-429x-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cardiovascular magnetic resonance in pregnant women: cross-sectional analysis of physiological parameters throughout pregnancy and the impact of the supine position

Abstract: BackgroundThere are physiological reasons for the effects of positioning on hemodynamic variables and cardiac dimensions related to altered intra-abdominal and intra-thoracic pressures. This problem is especially evident in pregnant women due to the additional aorto-caval compression by the enlarged uterus. The purpose of this study was to investigate the effect of postural changes on cardiac dimensions and function during mid and late pregnancy using cardiovascular magnetic resonance (CMR).MethodsHealthy non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 23 publications
6
51
0
8
Order By: Relevance
“…Besides, we demonstrated that there were no alterations in SV, CO, E, or E/A between the supine and the left recumbent positions. Our findings support Rossi's report, in which cardiovascular magnetic resonance failed to show any significant differences in left ventricular end-systolic or end-diastolic volumes in 5 non-pregnant women during the left recumbent position compared to the supine position (Rossi et al 2011). Therefore, in healthy young adults, a decrease in HR in the left recumbent position could be a physiological phenomenon that is not accompanied by changes in the circulation of the blood.…”
Section: Hemodynamics In the Heart And Inferior Vena Cava In Recumbensupporting
confidence: 91%
“…Besides, we demonstrated that there were no alterations in SV, CO, E, or E/A between the supine and the left recumbent positions. Our findings support Rossi's report, in which cardiovascular magnetic resonance failed to show any significant differences in left ventricular end-systolic or end-diastolic volumes in 5 non-pregnant women during the left recumbent position compared to the supine position (Rossi et al 2011). Therefore, in healthy young adults, a decrease in HR in the left recumbent position could be a physiological phenomenon that is not accompanied by changes in the circulation of the blood.…”
Section: Hemodynamics In the Heart And Inferior Vena Cava In Recumbensupporting
confidence: 91%
“…In particular, during the supine position the gravid uterus compresses the inferior vena cava resulting in restriction of venous return 1 , reduced ejection fraction, reduced cardiac output, and consequently impaired uterine perfusion. 2 Failure to prevent this compression can lead to maternal supine hypotensive syndrome (also known as inferior vena cava compression syndrome) 35 and ultimately to an adverse effect on gas exchange between mother and fetus with consequent fetal heart rate decelerations. 6 Since the 1950's it has been standard of care to place laboring pregnant women in the left lateral tilt position to displace the uterus from the inferior vena cava and thus improve maternal hemodynamics and gas exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Third-trimester Doppler studies in normal pregnant subjects showed no difference between CO measurements obtained in the lateral and those obtained in the supine position near term 31,32 . However, cardiovascular magnetic resonance (CMR) imaging showed a significant increment in left ventricle ejection fraction, SV and CO in the left lateral position in third-trimester pregnant subjects 33,34 . Therefore, it is strongly recommended that CO-related assessments are performed in the left lateral position from as early as 20 weeks' gestation.…”
Section: Cardiac Outputmentioning
confidence: 99%
“…CMR imaging has been evaluated in comparison with transthoracic echocardiography (TTE) in 34 pregnant women, and was shown to have higher reproducibility and smaller intra-and interobserver variability than TTE 80 . As with other methods, it is essential to position pregnant women in a left lateral position from as early as 20 weeks' gestation, as CMR studies have shown clearly the effect of caval compression by the pregnant uterus on CO 33,34 . A retrospective study by Romagano et al 81 showed that CMR findings, in addition to the findings by TTE, can alter the clinical management of pregnant women with complex cardiac disease or suspected aortic pathology.…”
Section: Cmr Imagingmentioning
confidence: 99%